(untitled) (Research, Society and Development, 2021)
The article aims to highlight the difficulties of the digital environment in Elementary School 1. Technology is a path to be followed by everyone involved in the school environment. The pandemic brought a lot of difficulty in relation to the technological environment as many families do not have access to the Internet. Despite technological evolution, there are still many children who have either had contact with a cell phone or computer, all these paradigms are related to digital exclusion and still face institutional exclusion, students are without access to the internet and are prevented from carrying out their school tasks, losing contact with the school. The digital exclusion poses great challenges to the school education of young people in elementary school I, and challenges teachers to enhance the perspectives of teaching and learning, however in Brazil we face important challenges, and it is extremely important to take different measures, so that students do not lose access to school. This exclusion happens in several ways and the increase in social inequality is visible, not everyone has the necessary structure to enter the virtual space, due to the lack of necessary equipment to monitor classes or because they do not have their own equipment to fulfill school tasks, some students tend to share the devices with family members. As for education, we need to understand that education is everyone’s right, the child is a developing being, and that their development is very fast at this stage, especially in the stages of elementary school 1. For her, everything is new, everything is experience.